THE ROLE OF ATG16L1 (THR300ALA) GENETIC VARIANTS AND AUTOPHAGY IN DEVELOPMENT OF ACUTE AND CHRONIC URINARY TRACT INFECTION CAUSED BY UROPATHOGENIC ESCHERICHIA COLI (Iraqi Journal of Medical Sciences, 2018)
Background: Uropathogenic Escherichia coli (UPEC) is the major cause of urinary tract infection (UTI), establish quiescent intracellular bacterial reservoirs (QIRs). These latent reservoirs, which persist indefinitely, are resistance to antibiotic therapies and can induce recurrence. Autophagy related 16 like 1 gene (ATG16L1) Thr300Ala genetic variant confer an increased risk for the development of urinary tract infection caused by UPEC. This study aimed.Objective: To determine the possible relationship between the ATG16L1 Thr300Ala genetic variant and UPEC for the development of acute and chronic urinary tract infection.Methods: A total of 100 urine and blood samples were collected from patients complain from UTI, 20 blood samples of apparently healthy during the period between (November 2014 to May 2015) from two hospitals in Baghdad; Al-Imamein Al-Kadhimein Medical City and Al-Yarmauk Teaching Hospital. The age range exactly with mean ± SD or SE. E. coli were isolated by ordinary methods and the identification of non entero-pathogenic E. coli was performed at a group level by slide agglutination test with specific antisera. UPEC isolates were tested for their susceptibility to 12 antimicrobial agents by disc-diffusion method. ATG16L1 T300A genotyping was done by Species Specific Primer – Polymerase Chain Reaction (SSP-PCR), after genomic DNA extraction from each blood sample. Results: A total of sixty E. coli were isolated from 20 acute UTI (16 females and 4 males) and 40 chronic UTI (32 females and 8 males). There is a high rate of acute UTI among the age range exactly groups (?10-20 years) and chronic UTI among age groups (21-40 years). Overall isolates had a complete resistance to Ampicillin and Gentamycin (100%), high resistance to Nalidixic acid (88%), Piperacillin (86%), Trimethoprime+Sulfa (84%), Cefotriaxon (80%), Ciprofloxacin (78%) and Cephalosporin (66%). Moderate resistance to Azithromycin (51%) and Cephalothin (50%) were seen. Whereas these isolates were highly susceptible to Imipenem and Nitrofuranton with the resistance rate 8% & 27% respectively. Ninety percent of the isolates were resistant to three or more antibiotics. The SSP-PCR result showed that a (89%) and (92%) of acute positive E. coli infection (P=0.009) and chronic positive E. coli infection (P=0.006) respectively were carried allele-G. While the occurrence of allele-G was (62%) in acute negative E. coli infection, and (30%) in chronic negative E. coli infection.Conclusion: There is a relationship between allelic variants of ATG16L1 gene with acute and chronic UTI. In the other hands, the risk of the present allele G was associated with increased susceptibility to infection by UPEC, which developing chronic and acute UTI.Keywords: Escherichia coli, autophagy, Thr300Ala genetic variant, PCRCitation: Abd GH, Abd Al-Rahman TR, Ghazi HF, Kadhim HS. The role of ATG16L1 (Thr300Ala) genetic variants and autophagy in development of acute and chronic urinary tract infection caused by uropathogenic Escherichia coli. Iraqi JMS. 2017; Vol. 15(4). 396-403. doi: 10.22578/IJMS.15.4.10
Keywords: Escherichia coli; autophagy; Thr300Ala genetic variant; PCR